Increase in the age of Olympic swimmers in modern times - Mazzilli, F. M. (The Journal of Strength and Conditioning Research, 2017)
Anecdotal data suggest an increase in the age of Olympic swimmers, but scientific studies in this regard are scarce, despite the importance for coaches of the confirmation of this increase in different styles. To ascertain the reality of this increase, this study focused on the analysis of the data contained in the reports of the Internal Olympic Games Association, covering different events and styles throughout the history of the Games. Starting with the 1908 Games, a total of 806 swimmers (436 men and 370 women) were included in the study. Of them, 137 men and 135 women had won 2 or more medals. Plots of the age of the swimmer at the time a gold, silver, or bronze medal was granted versus year of competition elicited statistical significant increases in 3 events in men and 9 events in women. Interestingly, significant increases were regularly observed in the styles introduced in the 60s, and a kind of V-shaped distribution was observed in some of the long established competitions, namely in the 100, 400 and 1,500 m freestyle in men, where the point of inflexion seems to occur around 1960. Overall, there is a continuing increase in the age of swimmers of ages over 24 years mirrored by a decrease of those younger than 20 years, and this is accompanied by the increased presence of swimmers that have won medals in 2 or 3 different Games.